IMPROVING PKK CADRES LEVEL OF KNOWLEDGE OF ANTIBIOTIC MANAGEMENT THROUGH PHARMACISTS-DELIVERED EDUCATION INTERVENTION IN BOJONGSARI, BANYUMAS - Masita Wulandari Suryoputri; Heny Ekowati; Ika Mustikaningtias; Laksmi Maharani; Nialiana Endah (Jurnal Farmasi Sains dan Praktis, 2022)
The prevalence of infectious diseases in Indonesia is high, so it can increase the use of antibiotics. The use of antibiotics which is around 40-60%. Inaddition to relatively long antibiotic therapy regimen, the lack of public knowledge in the rational use of antibiotics can cause patients to be less the risk of occurrence of antibiotic resistance, this study aims to determine the level of knowledge of PKK Cadres and to determine the level of community knowledge after providing PKK Cadres education with pharmacist assitance on antibiotic management. PKK cadres are the driving force behind village communities to carry out local health programs. The research method is a comparative descriptive with a cross sectional approach using an instrument in the form of a questionnaire and it is carried out before and after the implementation of pharmacist education. Collecting data by purposive sampling. Knowledge data of pretest and posttest were analyzed bivariately. The results of the evaluation of the education process indicated that there was an increase in the knowledge of PKK Caders. The results of pre-test dan post-test average showed increased of knowledge among PKK cadres from 69.28 to 85. The results of Wilcoxon test showed a significant difference in the PKK cadres level knowledge from the pre-test and post-test data of antibiotic management after receiving education from the pharmacist (p<0.005). Providing education on antibiotic management to PKK cadres by pharmacists has increased PKK cadres’ knowledge of antibiotic management. It is hoped that PKK cadres can disseminate this knowledge to the wider community to preventing antibiotic resistance.